2008
DOI: 10.3998/ark.5550190.0009.f06
|View full text |Cite
|
Sign up to set email alerts
|

Water promoted catalyst-free anti-Markovnikov addition of thiols to styrenes

Abstract: A facile and convenient catalyst-free method for the anti-Markovnikov addition of thiols to styrenes at room temperature in water has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 6 publications
0
2
0
3
Order By: Relevance
“…Other addition reactions. Movassagh et al reported a simple and efficient catalyst-free protocol for the anti-Markovnikov addition of thiols to styrenes at room temperature (Scheme 21), 198 yielding the corresponding adducts in good to excellent yields (54-98%). Interestingly, the use of other solvents, including MeOH, CHCl 3 , THF, and n-hexane, or performing the reaction under solvent-free conditions provided lower yields to those obtained in aqueous media.…”
Section: Aldol Reaction Of Thiazolidinedionesmentioning
confidence: 99%
“…Other addition reactions. Movassagh et al reported a simple and efficient catalyst-free protocol for the anti-Markovnikov addition of thiols to styrenes at room temperature (Scheme 21), 198 yielding the corresponding adducts in good to excellent yields (54-98%). Interestingly, the use of other solvents, including MeOH, CHCl 3 , THF, and n-hexane, or performing the reaction under solvent-free conditions provided lower yields to those obtained in aqueous media.…”
Section: Aldol Reaction Of Thiazolidinedionesmentioning
confidence: 99%
“…One of the popular approaches of styrene functionalization involves CC double bond functionalization. 5 However, C(Ar)–C(alkenyl) single bond functionalization is more challenging due to its high bond strength 6 and remains comparatively less studied. 7 Styrene has been employed here in a C–C single bond thioamidation reaction with a dithiocarbamate salt in the presence of ammonium persulfate and molecular oxygen from air without using any transition-metal catalysts (Scheme 1b).…”
Section: Introductionmentioning
confidence: 99%
“…)etil fenil tioéter [201] CG-MS (m/z, M +• 248), picos mayoritarios encontrados: 248 (64 %), 139 (2%), 123 (100 %), 103 (10 %), 77 (9 %).…”
Section: -(4-clorofenilunclassified
“…[257] La adición de tioles (R-SH) a dobles enlaces (C-C) mediante mecanismo radicalario (vía A) transcurre fácilmente bajo condiciones suaves de reacción y es conocida en la bibliografía. [201,256,[258][259][260][261][262][263][264][265][266][267][268][269][270][271][272] Este proceso da lugar exclusivamente a la formación del regioisómero anti-Markovnikov y generalmente se lleva a cabo en presencia de un iniciador radicalario (AIBN) o simplemente luz. [201,256,[258][259][260][261][262][263][264][265][266][267][268][269][270][271][272] En cambio, la adición del tiol al doble enlace en sentido Markovnikov [257] tiene lugar sólo cuando se utilizan cantidades estequiométricas de ácidos Brønsted tales como H 2 SO 4 en medio ácido acético, [273,274] ácido p-toluensulfónico [275] y HClO 4 , [203] ó de ácidos Lewis como TiCl 4 , [276] y AlCl 3.…”
Section: Introductionunclassified
See 1 more Smart Citation